Seroprevalence and some Demographic Factors Associated with Toxoplasma gondii Infection among Male Population in Duhok Province/Iraq - Eassa et al. (مجلة بغداد للعلوم)
The present study aims to investigate the seroprevalence rate of Toxoplasma gondii infection and its relation to some demographic factors among males in Duhok province/Iraq. A total of 424 random blood samples were collected from the male population of different ages (18-60) years and different social-economic classes. Out of 424 samples examined, 108 (25.47%) were seropositive to the anti- T. gondii antibodies; 88 (20.75%) were found seropositive for IgG, while 20 (4.72%) samples were seropositive for IgM. Regarding occupation, the highest percentage for chronic toxoplasmosis was reported in workers followed by policemen and pensioners at rates of 23.96%, 23.6%, and 23.07%, respectively. The age group 18-30 years showed the highest seropositive rate which was 26.6%; the seropositivity rate decreased with the increase of age. Regarding the blood groups, the highest percentage of IgG was reported in both O+ and B- groups, which were 23.2% and 23.1%, respectively. The higher rate of seropositivity was observed among married males (21.32%) as compared to unmarried males (19.05%) and fertile (22.3%) versus sterile males (12.5%). Concerning IgM antibodies, the highest seropositivity (9.4%) was reported in infertile males. The results of this study showed the importance of demographic factors to the epidemiology of T. gondii in males, which support the role of public health in the control of infectious diseases.